(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
Dystopian fiction is a complex literary genre that reflects social and political realities through imagined future worlds. Translating such texts is particularly challenging due to their dense ideological content, symbolic language, and unique stylistic features. This paper investigates the major challenges involved in translating dystopian fiction, focusing on terminology and stylistic expression in George Orwell’s 1984 and Ray Bradbury’s Fahrenheit 451. The study applies a qualitative analytical method to selected excerpts, examining how translators deal with neologisms, metaphors, and narrative tone. The results show that successful translation requires a careful balance between linguistic accuracy and creative adaptation. The paper also emphasizes the importance of cultural awareness in preserving the original meaning and emotional impact of the texts.